Tourist assessment of nightlife in Zagreb through TripAdvisor reviews - Raič, Marko; Jelinčić, Daniela Angelina (Turyzm/Tourism, 2026)
The night-time economy (NTE) refers to urban activities occurring between 6:00 PM and 6:00 AM, mainly focusing on activities related to nightlife venues (bars, clubs and coffee shops), creative industries (concerts and other musical events, theaters, festivals, cinema screenings, museums and galleries) and supporting activities such as hospitality, health services, transportation, delivery services, telecommunications, etc. It is very powerful in the context of tourism development, but precise statistics on the night-time economy are not readily available due to methodological challenges in its assessment. Still, its contribution to urban development is undoubted. Nightlife is an important aspect of the broader concept of the NTE and may have an important impact on the destination image. It is not easy to examine how tourists perceive nightlife experiences, but TripAdvisor offers significant insights into it, however, not many studies have analyzed tourists’ TripAdvisor reviews on nightlife experiences. Croatia has a prominent tourist industry and its capital, Zagreb, is the national center of creative industries. The aim of this study is to analyze how tourists evaluate their nightlife experiences there. So far its nightlife has not been systematically researched so this study has the goal of understanding which environment-related factors influence such experiences, and which nightlife images tourists assign to this city. Based on this, recommendations for policy makers and NTE professionals can be drawn. The methodology applied was aspect-based sentiment analysis (ABSA) of TripAdvisor reviews of the city’s clubs and bars in the three-year period (2022–2024), which was conducted in Python. Findings are classified into the following categories: social, sensory, cultural, safety and economic and the results show that the aspects of Zagreb nightlife mentioned most often are social- and sensory-related, being the factors that most strongly influence it. Safety-related reviews are not often considered while the economic-related dimension recorded the highest share of positive sentiment. Overall, the image that tourists assign to Zagreb’s nightlife is related to friendliness, affordability and vibrancy. The contribution of the study is seen in findings which may be used for the improvement of Zagreb nightlife and NTE as well as in tourism policy making.